Magnetic and Porous Nanospheres from Ultrasonic Spray Pyrolysis. - Won Hyuk Suh; Suslick, Kenneth S. (Journal of the American Chemical Society, 2005)
We have used an inexpensive high-frequency ultrasound generator from a household humidifier to create a useful source for ultrasonic spray pyrolysis and produced submicrometer silica particles that are porous on the nanometer scale. By using two heated zones, we first initiate polymerization of organic monomers in the presence of silica colloid, which creates in situ a composite of silica with an organic polymer, followed by a second heating to pyrolyze and remove the polymer. The morphology and surface area of the final porous silica are controlled by varying the silica-to-organic monomer ratio. In a single flow process, ferromagnetic cobalt nanoparticles can be easily encapsulated in the porous silica, and the resulting nanospheres are extremely resistant to air oxidation. Products were characterized by SEM, (S)TEM, EDS, XPS, and SQUID.